Maxim Violation by Indonesian Government Officials with Different Cultures in TV Talk Show - Meriani Meriani; Berlin Sibarani (Journal of Language, Literature and Teaching, 2019)
This research aimed at describing the violation of Grice Maxim’s Cooperative Principle by the three government officials in a TV Talkshow. Mata Najwa Talk Show and to seek out if the assumption of the different cultures would be the reason why the subjects violated the maxim. To achieve the purpose, this research was designed with descriptive qualitative. Its data were collected with documentary techniques in which the data were collected from the utterances between the host and the subjects in Mata Najwa Talk Show videos. To analyze the data Miles’ and Huberman analysis model was applied. The results of the research showed that not all of the officials violated the maxims. LBP violated all of the maxims, but JK did not, he violated the only maxim of quantity, quality, and relevance. JW did not violate all the maxim either. He violated the only maxim of relevance and maxim of quantity. The matrices showed that the different choice of what maxim to be violated was caused by their different culture. In the violation of more than one maxims, the three government officials did the violation in a different sequence. LBP firstly obeyed the M.of Rl and violated the M.of Qn, Meanwhile JK tends to violate M.of Qn and violated M.of Rl and Jokowi violated the M.of Rl and obeying the M.of Qn. These differences were due to the factor of social status, culture, education experience and awareness of the communication format of talk show, in which the participants are of three partied, namely host, guest, and TV audience all over Indonesia.